Development of a global framework for OHS professional practice. (August 2019) - Pryor, Pam; Hale, Andrew; Hudson, Dennis
Highlights: Lack of role clarity inhibits occupational health and safety profession. Global OHS Capability Framework developed through international collaboration. Global OHS Capability Framework defines professional boundaries. Global OHS Capability Framework provides a defines roles and career structure. Global OHS Capability Framework provides a basis for professional education. Abstract: There have long been discussions on the professionality of occupational health and safety (OHS) and concerns about standards of practice, with the recognition of OHS as a profession further inhibited by lack of clarity on role and variations in terminology and principles underpinning practice. In 2013, the International Network of Safety and Health Practitioner Organisations (INSHPO) recognized the need for a global approach to reconceptualise OHS professionals as influential leaders who can work to integrate OHS within business processes. The Occupational Health and Safety Professional Capability Framework: A Global Framework for Practice was subsequently developed by this international body representing OHS professional associations across 10 countries with the outcome endorsed by 53 organisations at a ceremonial signing of the Singapore Accord. This paper reviews the development of the framework and the emergence of two clear roles; the OHS Professional and OHS Practitioner. It explores the process for clarifying the roles and required knowledge and skills together with the challenges experienced along the way. The paper recognises that the framework should not be a static document and so concludes by considering the work still to be done.